Students’ Perception towards Online Learning across Multiple Disciplinary Courses in India—A Qualitative Analysis - Lakshmi Devasena C; Shubhangi V Urkude (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Online learning has become essential to the teaching and learning approach during the pandemic. Due to its enormous benefits, online or e-learning can be sustained. The acceptability of online or e-learning depends on the student’s perception and the availability of infrastructure. Data from various streams and age groups has been collected from students in different institutions. After collecting the data, this research incorporates descriptive statistics for a thorough analysis and utilizes the Chi-square test to provide scientific evidence. This study finds that the majority of final-year undergraduate and postgraduate students support online education. The student’s economic status affects their preference for online or e-learning. Having a smart device and internet access also influence the decision to pursue online or e-learning. Gender is positively associated with access to Internet facilities and has a cascading effect on preferences for online or e-learning. Female students prefer online classes but require additional internet resources. Higher education institutions could enhance their online course offerings by targeting specific groups, such as female students for postgraduate programs, if they could better understand their preferences. Even though some existing studies in the literature have examined the Indian scenario to understand the factors influencing the adoption of online education, none of these studies have considered the fundamental need for online or e-learning. Moreover, the preferences were not studied based on different demographics. This research work has collected and utilized data from various educational disciplines across multiple institutes, marking the first endeavor of its kind in the literature.